Functional Analysis and Validation of a UAM Integrated Flight Management (UIFM) System - Lee, Youngjae; Gwak, Chan; Bae, Sangyeul; Park, Kyu Ri; Lee, Hyeon Jun; Lee, Jae-Woo (International journal of aeronautical and space sciences, 2024)
A real-time flight management system needs to be established to allow urban air mobility (UAM) vehicles to fly safely at low altitudes in areas containing many obstacles. In this study, a UAM integrated flight management (UIFM) system is designed to manage the flight operations of UAM vehicles. Depending on the stakeholders involved, the UIFM system may be composed of various modules, such as the UAM air traffic management (UATM), UAM ground traffic management (UGTM), and UAM flight operations management (UFOM) modules. The tasks and functions of these three modules were analyzed and defined, and the functions at the initial stage of development were implemented in the form of software. This software was then applied to an operational digital twin (ODT) system equipped with a simulation environment. Operational procedures were established to validate the suitability of the route adherence monitoring (RAM) function, and this validation process was executed using the ODT system. As a result, it was found that the RAM function of the UIFM system operated appropriately according to the scenarios considered.